2021
DOI: 10.1093/asj/sjaa418
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Safety and Efficacy of a 1060-nm Diode Laser for Non-Invasive Fat Reduction of the Abdomen

Abstract: Background Despite the proven efficacy of liposuction, there is a population of patients who prefer non-surgical alternatives. Laser hyperthermia-induced lipolysis has emerged as one non-invasive alternative to liposuction. Objectives The authors sought to evaluate the safety and efficacy of a 1060-nm (±10 nm) diode laser for non-invasive fat reduction of the abdomen. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…33 Ultrasound after 1060-nm diode laser treatment showed that abdominal adiposity was reduced by 4.92% at 6 weeks and 8.55% ( P < 0.0001) at 12 weeks posttreatment. 3 However, ultrasound found no statistically significant reductions after LLLT 38 and, paradoxically, thickness increased in some participants. Using 3-dimensional photography 4 and comparing vs control, a statistically significant absolute fat volume loss of 56.2 mL ( P < 0.0001) was observed 2 months after cryolipolysis, as well as a mean absolute difference of 39.6 mL between treated and control areas.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…33 Ultrasound after 1060-nm diode laser treatment showed that abdominal adiposity was reduced by 4.92% at 6 weeks and 8.55% ( P < 0.0001) at 12 weeks posttreatment. 3 However, ultrasound found no statistically significant reductions after LLLT 38 and, paradoxically, thickness increased in some participants. Using 3-dimensional photography 4 and comparing vs control, a statistically significant absolute fat volume loss of 56.2 mL ( P < 0.0001) was observed 2 months after cryolipolysis, as well as a mean absolute difference of 39.6 mL between treated and control areas.…”
Section: Discussionmentioning
confidence: 87%
“… 2 Furthermore, many patients may decline or be unsuitable for surgery. 3 Liposuction also risks long recoveries, scars, hematomas, 4 , 5 and complications such as bowel perforation 6 or long-term and/or potentially fatal deep vein thrombosis and pulmonary embolism. 4 , 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study looking at diode treatments found that a single treatment with a diode laser can reduce adipose tissue by 8.55% at 12 weeks post-treatment. 10 Pulsed electromagnetic fields (PEMFs) are induced by short pulses of electrical current that penetrates the skin and results in the stimulation of molecular and cellular activities. Pulsed electromagnetic fields increase collagen fiber production by dermal fibroblasts and stimulate angiogenesis, leading to wound-healing effects.…”
Section: Discussionmentioning
confidence: 99%
“…This process of heat‐induced adipocyte apoptosis, followed by removal by macrophages, allows a specific reduction of the fat layer. One study looking at diode treatments found that a single treatment with a diode laser can reduce adipose tissue by 8.55% at 12 weeks post‐treatment 10 . Pulsed electromagnetic fields (PEMFs) are induced by short pulses of electrical current that penetrates the skin and results in the stimulation of molecular and cellular activities.…”
Section: Discussionmentioning
confidence: 99%